2007
DOI: 10.1107/s1600536807043097
|View full text |Cite
|
Sign up to set email alerts
|

DL-Aspartic acid

Abstract: CommentInterest in D,L-aspartic acid has spanned several decades, from the first structural determination by Rao (1973), due to its acting as important ligand in the preparation of transition metal complexes (Ciunik, 1987;Casellato et al., 1991;Barfod et al., 1999). In exploring the possibility of introducing D,L-aspartic acid into a phosphite system, we unexpectedly obtained the title compound. To the best of our knowledge, there are only four reports on the structure of D,L-aspartic acid (Rao et al., 1968;Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
(12 reference statements)
1
12
0
Order By: Relevance
“…As shown in Figure , the crystal periodicity is given by the unit cell dimensions and is indicated by two orthogonal arrows. The FFT spectrum is shown in the top right inset, and the indicated periodicity is 0.74 and 0.91 nm, which are in agreement with the values for bulk periodicity …”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…As shown in Figure , the crystal periodicity is given by the unit cell dimensions and is indicated by two orthogonal arrows. The FFT spectrum is shown in the top right inset, and the indicated periodicity is 0.74 and 0.91 nm, which are in agreement with the values for bulk periodicity …”
Section: Resultssupporting
confidence: 84%
“…The FFT spectrum is shown in the top right inset, and the indicated periodicity is 0.74 and 0.91 nm, which are in agreement with the values for bulk periodicity. 18 Apparently the frequency of the precipitation pattern of amino acids is not equal for all configurations;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the authors stated that the new form "crystallizes in the same space group as the previously reported form but with a slightly different a axis." However, when inspecting the structure, it was found that the simple unit cell transformation (transformation matrix 1 0 2/0 1 0/0 0 À1) from the original cell as published by Rao (1973) yields the cell found by Wang et al (2007). Consequently it is evident that this crystal does not represent a novel phase.…”
Section: Aspartic Acidmentioning
confidence: 87%
“…Recently, a study proposed another "form of DL-aspartic acid" (Wang et al 2007). In this paper, the authors stated that the new form "crystallizes in the same space group as the previously reported form but with a slightly different a axis."…”
Section: Aspartic Acidmentioning
confidence: 93%